Emotional stress in pregnant women in the context of the Covid-19 pandemic (Research, Society and Development, 2021)
The aim of this study was to analyze the situations caused by the COVID-19 pandemic that aggravated emotional stress in pregnant women and how the Nursing team will provide assistance in these situations. This is an integrative literature review, through the guiding question: “How does the Nursing team develop care actions to try to reduce emotional stress in pregnant women during the pregnancy cycle during the pandemic?”, elaborated based on the method PICO, in three databases with the descriptors pregnant women, mental health, obstetric nursing and adaptation. Sixteen articles were included, twelve being national, four in English and zero in Spanish, with years of publication from 2018 to 2021. Nursing will develop care through telenursing, compressing prenatal care in virtual consultations and visiting them only when necessary and wearing mandatory attire, providing for the safety of the pregnant woman and the shortest possible physical contact time in order to avoid the possibility of transmission of COVID-19. Professionals will be able to use the Fear Scale for the Perinatal Period to assess the fear of pregnant women regarding COVID-19 so that they can accurately guide, welcome and refer the woman in the pregnancy period with aggravated emotional stress. Therefore, pregnant women can be calm in the face of their fears, as the Nursing team is present and prepared to deal with differences together with them.